Strengthening the search for information for homemakers in situations of information overload - Halimah, Lien; Rullyana, Gema; Ardiansah, A. (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
Information retrieval in a vital information retrieval system process learned by homemakers. Especially information relating to households. The service method implemented uses strengthening information retrieval based on interview results. The results of the interviews illustrate that the retrieval system is a series of system processes in carrying out information retrieval activities until documents or information are found based on queries so that they can meet user needs and satisfy requests for information from users. The steps in carrying out information search activities, namely: starting, chaining, browsing, differentiating, monitoring, extracting, verifying, and ending. Then to become community information, the community must be able to make changes. For example, there is progress in information, one of which is in the field of education. Strengthening is done by strengthening people's behavior towards information-seeking ways to avoid hoaxing information during an information overload.